Diseño de un sistema de gestión de mantenimiento para una empresa constructora que se dedica a la elaboración de vías lastradas en la provincia del Guayas - Quinde Rang, Ronald (2010)
Nowadays, companies seek perfection in their processes through strategies and methodologies that are designed now. That is why that in Ecuador the industry is gradually restructuring with new strategies and methodologies and thus achieves to be competitive worldwide. Was developed an analysis of the current situation of the company which identified critical assets, Based on this, was performed the design of maintenance management system that is presented in two parts: Technical and Administrative Management that describes where and how will organize, plan, manage and control maintenance. It is based on Total Productive Maintenance (TPM), with key indicators of maintenance, failure mode analysis, work orders and maintenance plans. Human Talent Management presents the design of the strategy of the 5 S's, Matrix of Skills, Training Plan. In the end it presented the conclusions and recommendations that enable effective implementation of the system by the company, which is projected at least 90% the availability of equipment.